(untitled) (Communications in Mathematical Research, 2021)
In this paper we derive the fundamental inequality of the theorem of meromorphic functions. It extends some results of Yi Hong-xun et al. As one of its applications, we then study the value distribution of f^(k) f^n - c(z).